2020
DOI: 10.3390/foods9060745
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Consumers’ Purchase Intention of an Innovation of the Agri-Food Industry: A Case of Artificial Meat

Abstract: Green consumption is an emerging environmental topic receiving global attention. Because livestock production is a primary source of greenhouse gas emission, the “low-carbon diet” has become a new trend in the catering industry. Fast food companies have been launching vegetarian products because artificial meat requires less water and land resources than traditional livestock and has lower carbon emissions. This study explores the influence of consumers’ attitude, subjective norms (SNs), and perceived behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 73 publications
2
19
1
1
Order By: Relevance
“…For the majority, a smart diet and high-quality goods are preferable [5]. In studies related to personal aspirations and social norms, regarding social commitments, consumers displayed one-sided perceptions [6]. Generally, people should not attempt to hide their real perceptions of an object for various reasons, such as the fact that an individual can demonstrate a positive identity within society.…”
Section: Background Of the Studymentioning
confidence: 99%
“…For the majority, a smart diet and high-quality goods are preferable [5]. In studies related to personal aspirations and social norms, regarding social commitments, consumers displayed one-sided perceptions [6]. Generally, people should not attempt to hide their real perceptions of an object for various reasons, such as the fact that an individual can demonstrate a positive identity within society.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Not surprisingly this has led us to consider eating meat as natural, normal, necessary, and nice [ 2 ]. It is only recently that meat came under intense scrutiny which increasingly highlighted the detrimental impact of meat production and consumption on animal welfare, human health and the environment [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. However, despite this scientific evidence, meat demand is expected to further increase in the coming years [ 10 , 11 , 12 , 13 ], putting intense strain on our already exhausted ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…According to Scalco et al [30], the most important social influences related to consumers' environmentally friendly food purchases are from their families, friends, colleagues, and other reference groups. Previous research indicated that subjective norm is a positive driver of consumers' behavioural intentions to indulge in their food choices [31,32]. However, other scholars [19,33] argue the efficacy of subjective norm in explaining consumer food choices and agree that more examinations into the role of the subjective norm are needed.…”
mentioning
confidence: 99%